Melkersson-Rosenthal Syndrome: A Rare Cause of Recurrent Facial Nerve Palsy and Acute Respiratory Distress Syndrome - Behiye Deniz Kosovali; Asiye Yavuz; Fatma Irem Yesiler; Mustafa Kemal Bayar (Case Reports in Neurological Medicine)
Melkersson-Rosenthal Syndrome (MRS) is a rare disease characterized by persistent or recurrent orofacial oedema, relapsing peripheral facial paralysis, and furrowed tongue. Pathologically, granulomatosis is responsible for oedema of face, labia, oral cavity, and facial nerve. We present a patient with MRS admitted to our hospital with acute respiratory distress syndrome (ARDS). 45-year-old woman was admitted to an emergency department with dyspnea and swelling on her hands and face. She was intubated because of ARDS and accepted to intensive care unit (ICU). After weaning from ventilatory support, peripheral facial paralysis was diagnosed and steroid treatment was added to her therapy. On dermatologic examination, oedema on her face, pustular lesions on her skin, and fissure on her tongue were detected. The patient informed us about her recurrent and spontaneous facial paralysis in previous years. According to her history and clinical findings, MRS was diagnosed.